Optimalisasi Edukasi Kewirausahaan Sejak Dini Sebagai Daya Ungkit Inovasi MI Al-Mustawa Gunung Sindur Kabupaten Bogor - Widayani Wahyuningtyas; Aniek Irawatie; Suprima Suprima; Hermina Hermina; Hairunnisa Br. Sagala; Abdullah Arif (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This Community Service (PKM) program aims to optimize the instillation of entrepreneurial values ​​from an early age at Al Mustawa Elementary School (MI) in Gunung Sindur, Bogor Regency, as a lever for innovation at the school. This program was implemented to address the limited understanding of entrepreneurship, which was previously defined solely as "selling" activities. The research method used was descriptive qualitative, involving students in grades 4, 5, and 6, teachers, and parent representatives (the School Committee). Data collection techniques included participant observation, in-depth interviews, and documentation studies. The results of the PKM program indicate a shift in the entrepreneurial paradigm from mere transactions to the ability to identify opportunities and generate innovative solutions (innovation). The implementation of experiential learning methods (learning through experience) has proven effective in fostering student enthusiasm and creativity in identifying simple product ideas. This optimization is recommended to be continued through the establishment of a Little Creative Club and the integration of simple entrepreneurship modules into the madrasah curriculum